Pengaruh Pupuk Organik Cair Dari Limbah Air Kelapa (Cocos nucifera L) dan Daun Gamal (Grilicidia sipeum) Terhadap Pertumbuhan Bayam Merah (Amaranthus tricolor L): Effect of Liquid Organic Fertilizer from Waste Water of Coconut (Cocos nucifera L) and Gamal Leaves (Grilicidia sipeum) on the Growth of Red Spinach (Amaranthus tricolor L) - Lamusu, Darni; Nasriadi, Nasriadi (Babasal Agromu Journal, 2025)
The purpose of the study was to determine the growth response of the best treatment of liquid organic fertilizer from waste coconut water and gamal leaves to the growth of red spinach plants. This study uses a Group Random Design (RAK) with one factor, namely the application of POC of coconut water and gamal leaves with 4 levels of treatment repeated 3 times so that it becomes 12 polybags, namely as follows: P0 = POC of coconut water waste and gamal leaves 20 ml/500 ml of water, P1 = POC of coconut water waste and gamal leaves 25 ml/500 ml of water, P2 = POC of coconut water and gamal leaves 30 ml/500 ml of water, and P3 = POC of coconut water waste and gamal leaves 35 ml/500 ml of water. The result of this study is that the application of liquid organic fertilizer from coconut water waste and gamal leaves has a very real effect on the growth of red spinach plants, namely in height, number of leaves, stem diameter, and wet weight. The best treatment in this study was P2 treatment (POC of coconut water waste and gamal leaves, 30 ml/500 ml of water) on all variables such as height, number of leaves, stem diameter, and wet weight of red spinach. Keywords: POC, Coconut Water, Gamal Leaves, and Fertilizer.